Sovereign exposures in the Portuguese banking system: determinants and dynamics - Campos, Maria Manuel (2019)
This paper studies the dynamics of the exposure of the Portuguese banking system to the domestic public sector over 2008-2016 and assesses possible underlying motivations. The analysis relies on a new dataset built from granular information that provides full coverage of the Portuguese banking sector and the public sector. The results suggest that moral suasion was an important driver of the evolution of sovereign exposures during the euro area crisis: domestic banks provided financing to the sovereign when the Treasury needed to issue debt amidst rising yields and, although to a smaller extent, when State-Owned Enterprises faced funding shortages in international markets. Moreover, increases in central bank funding are also related to increases in holdings of sovereign debt securities. These findings mainly hold for medium-sized and large banks. In contrast, we find no evidence of gambling for resurrection behaviour by banks with lower prudential capital or depressed profitability.